URBANISASI DAN KEMISKINAN DI INDONESIA - Abdul Karim Jabbar; Fakhruddin Fakhruddin (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
AbstractThis study aims to analyze the relationship between urbanization and urban poverty in Indonesia. The data used is panel data from 5 provinces, namely Aceh, Bengkulu, Central Sulawesi, West Nusa Tenggara and Papua from 1980 to 2015. The analysis model used is a simple linear regression model. To decide which model is most appropriate to use in this study, the Chow and Hausman tests were carried out. Based on the results of the panel model test, it can be concluded that the most appropriate model to use is the Random Effect Model (REM). The results of the REM model approach show that urbanization and GRDP have a negative and significant effect on urban poverty. The results of this study are expected to provide input for policy makers in overcoming the excessive number of urbanization in the provinces in Indonesia. For further research that examines urbanization, other variables can be added so that the results are more indepth and comprehensive.Keywords: Urbanization, Poverty, and GRDP